Upaya Peningkatan Kualitas UMKM Makanan Olahan - Mai Hetti, Selvi (Jurnal Pengabdian Masyarakat Inovasi, 2024)
The development of Micro, Small, and Medium Enterprises (MSMEs) in the processed food sector is often hindered by low visual quality and conventional packaging systems. This community service activity aims to enhance the competitiveness of cassava chip MSMEs through packaging optimization and marketing strategies based on marketing research management. The method employed was action research, which included participatory observation, in-depth interviews with owners and employees, and distributing questionnaires to customers to map consumer perceptions. A SWOT analysis was used to formulate targeted business development strategies. The results indicated that the partner's primary strength lies in authentic taste, yet it suffers from weaknesses in packaging design and high oil residue. Through this program, business owners have gained technical knowledge regarding protective packaging materials and skills in designing attractive visual identities. The implications of this activity emphasize the importance of transitioning from conventional to modern packaging to increase market value and expand market share. It is recommended that continuous mentoring be provided on a larger scale to accelerate the digitalization of MSME marketing in Medan.